Amplificando el impacto del diseño a través de DesignOps - Mengoni Leon, Alexandra (2021)
DesignOps is born out of different needs in design teams. The value that design generates through their creative process, made that there is more demand for these profiles in organizations. However, the more design needs in their strategies, products and services, the greater the need for DesignOps due to all the operational and support tasks required for designers to focus on what they are passionate about: designing. DesignOps is responsible for amplifying the impact of the design team within an organization by helping them optimize processes, standardize tools, establish a culture in the team and support them in many other management issues. A practice that is constantly learning because of how new it is but with much to discover, execute, iterate and learn.